Main Values of Toba Muslim Batak Culture in Moral Education Perspective - Muhammad Abrar Parinduri; Abdul Karim; Hana Lestari (Institut Agama Islam Negeri Madura, 2020)
Islamic education has the primary goal of forming morals in order to fulfill things that are material and spiritual. This study emphasized the importance of learning science through education, especially those related to noble character, or better known as moral education. The novelty of this research is courses taught at PTAI to have a noble moral education content. This research used a library research approach. Besides, this study conducted data collection techniques by examining books, journals, literature, notes, and report variants related to the problem being solved. The results show that the main values of the Toba Batak culture include: kinship, hagabeon, hasangapon (glory, authority, and charisma), main value is hamoraon or wealthy, hamajuon, or progress, protection, arsisarian, or mutual understanding. We also concluded that there is no difference in the main cultural values of the Christian and Muslim Toba Batak people.